Consumo e desempenho de ovinos mantidos em pastagem de Cynodon dactylon var.dactylon com diferentes níveis de oferta de lâminas foliares verdes - Santos, Marcia Vendrusculo dos (2010)
The effect of different allowances (3, 6, or 9 kg of dry matter (DM)/100 kg of body weight (BW)) of leaf lamina (ALL) on the traits of a bermudagrass pasture Cynodon dactylon var. dactylon) and on the performance of sheep was evaluated. The experiment was conducted in five periods of 28 days, from october 2008 to february 2009, in a fully randomized arrangement with three replications of area per treatment and three tester sheep in each area. There was statistical interaction (P<0,05) between period and forage allowance for the following variables: forage mass (2.878 to 6.580 kg of DM ha-1), proportions of stem in the DM (22,2 to 52,9%), proportions of dead material in the DM (20,5 a 58,4%), and animal stocking rate (652 to 2.428 kg of BW ha-1). The ALL did not affect (P<0,05) the leaf proportion of the pasture (18,6 to 22,2%) and the growth rate of leaf lamina (12 to 39 kg ha -1 day-1 of DM). However, those variables varied quadratically and cubically (P<0,05) according to the periods, respectively. Herbage chemical composition also was not affected by the treatments, although the neutral detergent fiber content and the in vitro digestibility had varied quadratically (P<0,05), while nitrogen and dry matter content varied cubically (P<0,05) according to the periods. A statistical interaction between period and ALL was found for animal performance (P<0,05). Excepting the second experimental period where the average daily gain (ADG) ranged from 54 to 99 g animal-1 day-1, ADG presented negative values during the experiment. On the other hand, estimated forage intake was not affected by the ALL levels, and averaged 1.044 g of DM animal-1 dia-1. It was concluded that the ALL level of bermudagrass does not affected herbage growth, and irregularly influenced sheep performance. However, adverse climatic conditions during the experiment markedly influenced the results obtained.